Multiple transatlantic incursions of highly pathogenic avian influenza clade 2.3.4.4b A(H5N5) virus into North America and spillover to mammals - Erdelyan, Cassidy N.G.; Kandeil, Ahmed; Signore, Anthony V.; Jones, Megan E.B.; Vogel, Peter; Andreev, Konstantin; Bøe, Cathrine Arnason; Gjerset, Britt; Alkie, Tamiru N.; Yason, Carmencita; Hisanaga, Tamiko; Sullivan, Daniel; et al. (Cell reports (Cambridge), 2024)
Highly pathogenic avian influenza (HPAI) viruses have spread at an unprecedented scale, leading to mass mortalities in birds and mammals. In 2023, a transatlantic incursion of HPAI A(H5N5) viruses into North America was detected, followed shortly thereafter by a mammalian detection. As these A(H5N5) viruses were similar to contemporary viruses described in Eurasia, the transatlantic spread of A(H5N5) viruses was most likely facilitated by pelagic seabirds. Some of the Canadian A(H5N5) viruses from birds and mammals possessed the PB2-E627K substitution known to facilitate adaptation to mammals. Ferrets inoculated with A(H5N5) viruses showed rapid, severe disease onset, with some evidence of direct contact transmission. However, these viruses have maintained receptor binding traits of avian influenza viruses and were susceptible to oseltamivir and zanamivir. Understanding the factors influencing the virulence and transmission of A(H5N5) in migratory birds and mammals is critical to minimize impacts on wildlife and public health. [Display omitted] •Seabirds likely enabled multiple incursions of A(H5N5) virus from Europe to Canada•Some A(H5N5) viruses possessed the mammalian adaptation marker PB2-E627K•A(H5N5) viruses demonstrated rapid 100% mortality and some transmission in ferrets•A(H5N5) viruses preferred avian virus receptors and are sensitive to NA inhibitors Erdelyan et al. reveal that seabirds likely facilitated the spread of A(H5N5) viruses from Europe to Canada. All viral segments were Eurasian. Hemagglutinin contained substitutions not present in Canadian A(H5N1) viruses. These viruses remain susceptible to neuraminidase inhibitors. In ferrets, the virus caused rapid mortality, with some transmission to contacts.